DAMPAK KEBERADAAN JEMBATAN SURAMADU TERHADAP NILAI TANAH DI WILAYAH KAKI JEMBATAN SISI MADURA - Amanatuz Zuhriyah dan Ihsannudin (Agriekonomika, 2013)
The construction of Suramadu Bridge give an impact on land values in foot bridge areas. This study aims to analyze the impact of the bridge on land values, before and after presence of the bridge. The results of this research  shows land values at Labang is more than  before. While, land values at Arosbaya, as control areas, has not changed significantly before and after the construction. The comparison between subject areas and control areas before the construction, were not significantly different. While, after the construction, there are significant differences between two samples tested, indicating that the existing  Suramadu bridge has impact to the land value at Labang compared to land values at Arosbaya, as control areas.